Real-world retrospective comparison of 0.19 mg fluocinolone acetonide and 0.7 mg dexamethasone intravitreal implants for the treatment of diabetic macular edema in vitrectomized eyes - Coelho, João (2020)
Purpose: The aim of this study was to evaluate the long-term real-world effectiveness of FAc and DEX implants in vitrectomized DME eyes in a real-world setting. Methods: This was a non-interventional, retrospective, comparative study of 46 vitrectomized eyes in 33 patients with persistent or recurrent DME quantified best-corrected visual acuity (BCVA), central foveal thickness (CFT) and intraocular pressure (IOP) over up to 37 months. Results: Both FAc and DEX treatment led to statistically and clinically significant improvements in BCVA and CFT. FAc >10-letter improvement on the Early Treatment Diabetic Retinopathy Study [ETDRS] chart over months 3-24 and a sustained ~200 µm CFT reduction over months 1-24; DEX: >5-letter improvement on the ETDRS chart at months 1 and 3 and >100 µm CFT reduction at month 1. FAc demonstrated sustained, stable and predictable effects on BCVA and CFT over 24 months and also improved BCVA and decreased CFT in a cohort of DME eyes that was refractory to DEX over 6 months. Conclusion: This real-world study demonstrates long-term effectiveness of FAc in vitrectomized DME eyes and sustained effectiveness in DME eyes that did not respond to DEX therapy.